Concept As a Cognitive and Linguistic Category - Nargiz Nazarova (Periodica Journal, 2022)
This article describes the concept as a unit of linguocognitive and linguocultrological linguistics based on the descriptions and classifications of scientists.
Keywords: lingvocognitive; concerpt; lingvocultrological; linguistics